Biocontrol of pea root rot incited by Fusarium so/ani f. sp. pisi with rhizosphere mycoflora - B.L. JALALl, P.K. JHA* and (Indian Phytopathology, 2006)
The root rot disease of pea (Pisum sativum L.) incited by Fusarium solani f.sp. pisi cause considerable crop losses in northern India. The fungal isolates of pea rhizosphere were evaluated for their biocontrol potential against Fusarium solani f.sp. pisi under in vitro study (dual culture method) and sick soil (pot) condition. Under in vitro study, isolate Trichoderma viride showed the strongest antagonistic activity towards F. solani f.sp. pisi in dual culture followed by Aspergillus niger. A. terreus, A. sydowi, A. flavus and Spicaria sylvatica. The two highly efficient antagonists- T. viride and A. niger were studied individually and in combinations in relation to the biocontrol of pea root rot under pathogen sick soil (pot) condition. Both the antagonists controlled the disease more efficiently when used individually than those used in combinations. T. viride and A. niger applied individually @15 gm/5kg sick soil recorded the disease severity of 33.3% and 40% respectively, while the disease severity under untreated sick soil was 96.6%.